Rechterlijk Pardon and the Enforcement of Tax Crimes: A Normative Framework to Strengthen State Financial Recovery - Leo Satria Eka Putera; Ino Susanti (CV. Norma Global, 2026)
Rechterlijk pardon was introduced by Law No. 1 of 2023 as a new sentencing mechanism that allows judges to declare a defendant guilty without imposing punishment when substantive justice favors leniency. Although this mechanism applies generally to criminal cases, its relevance for tax crime enforcement has not been examined, particularly in relation to the restorative orientation of the Law on General Provisions and Procedures for Taxation (UU KUP). This study employed normative legal research to evaluate the doctrinal foundation, practical implications, and policy relevance of applying rechterlijk pardon in tax crime cases where the recovery of state financial losses is the primary objective. The findings indicated that existing administrative pathways in Article 8 paragraph (3) and Article 44B UU KUP facilitate fiscal recovery but do not address situations in which criminal liability is proven yet imprisonment is disproportionate. Rechterlijk pardon has the potential to harmonize restorative justice principles with efficient tax enforcement, although its application requires clear safeguards to prevent moral hazard and maintain deterrent effect. This article constructed a conceptual framework outlining conditions under which judicial pardon may be appropriate in tax crime cases and argued that regulatory alignment between UU KUP and the new KUHP is essential for ensuring legal certainty and accountability.